Gestión de talento humano en el Gobierno Autónomo Descentralizado Parroquial Rural de San Juan en el período 2022 – 2023. - Vera Álava, Ashley Noemi (2024)
This case study refers to the aspects of human talent management in the Rural Parochial Decentralized Autonomous Government of San Juan in the period 2022 - 2023, it faces some challenges, one of them and the limitation of resource capacity. which makes it difficult to implement talent development programs and retain qualified personnel. Additionally, the lack of specialization in human resources can result in inefficient selection processes and the inability to identify and develop employees' potential. Professional development is limited by the lack of training opportunities. Internal communication is also a challenge, as importance hinders the flow of information. The variety of roles in the parish makes talent management difficult. The lack of incentives affects staff motivation and their commitment to the company's goals. Solutions adapted to the context of the parish are needed to overcome the challenges and thus improve human talent management.